Pemanfaatan Buku Kesehatan Ibu Dan Anak Oleh Ibu Hamil Trimester III - Eni Kurniawati; Ari Sulistyawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Maternal Mortality Rate (MMR) in Bantul regency in 2011 increased compared to the year 2010 is 82.07 / 100,000 live births in 2010 to 111.2 / 100,000 live births and the infant mortality rate (IMR) of 8, 5/1000 KH in 2011. Policy and government efforts to reduce maternal and infant mortality, among others, the activities of Mother Friendly Movement (GSI), Strategy Making Pregnancy Safer (MPS) and the procurement of KIA books. KIA book than as a record of maternal and child health, health monitoring tools and means of communication between health workers with patients.Objective: To learn about the utilization of Mother and Child Health (MCH) books by pregnant women in health centers Sewon I.Methods: Type of research is a descriptive study with cross sectional approach. Entire third trimester pregnant women during the month of January to May in Puskesmas Sewon I counted 65 people in 2013, while the sample 40 pregnant women who met the inclusion criteria. Collecting data using questionnaires. Results were analyzed using univariate analysis.Results: Utilization of MCH books seen from the level of knowledge of pregnant women about the books in the category KIA higher by 92.5%, a high level of understanding in the category as much as 67.5%, and visits as recommended by the government as much as 87.5%. Characteristics of pregnant women in the third trimester I Puskesmas Sewon Bantul, Yogyakarta mostly between the ages of 21- 35 years by 85%, the majority of pregnant women educated at the high school last / equal as much as 45%, the majority of pregnant women have parity ≤ 2 by 67, 5%, and the majority of pregnant women living as a Housewife (IRT) as much as 65%.Conclusions: most of pregnant women use MCH book as a media to help them know about their health.Keywords: Utilization of MCH books